2020
DOI: 10.1080/02671522.2020.1723679
|View full text |Cite
|
Sign up to set email alerts
|

Bystander behaviour in peer victimisation: moral disengagement, defender self-efficacy and student-teacher relationship quality

Abstract: The aim of this study was to examine how different bystander roles in peer victimisation situations relate to moral disengagement, defender self-efficacy, and student-teacher relationship quality. Self-reported survey data were collected from 333 middle and junior high school students (10-15 years of age) from four schools in Sweden. Random intercept model analyses of factor scores revealed that, when witnessing peer victimisation, students high in moral disengagement and low in defender self-efficacy were mor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

14
33
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 40 publications
(50 citation statements)
references
References 66 publications
(120 reference statements)
14
33
0
Order By: Relevance
“…Thus, our study suggests that the capacity to enact moral agency among students when they are witnessing school bullying is dependent on their beliefs in their individual capacities to successfully intervene and help the victim, which, in turn, supports the social-cognitive theory of moral agency (Bandura 2016). In accordance with our hypothesis and a few previous studies (Pöyhönen et al 2012;Sjögren et al 2020;Thornberg and Jungert 2013), defender self-efficacy was found to be linked to greater reinforcing, even though the link was weak. Thus, low defender self-efficacy does not only inhibit defending and increases the risk that students remain passive as bystanders (e.g., Thornberg and Jungert 2013;Thornberg et al 2017) but also that they laugh and cheer on the bullies.…”
Section: Defender Self-efficacysupporting
confidence: 92%
See 3 more Smart Citations
“…Thus, our study suggests that the capacity to enact moral agency among students when they are witnessing school bullying is dependent on their beliefs in their individual capacities to successfully intervene and help the victim, which, in turn, supports the social-cognitive theory of moral agency (Bandura 2016). In accordance with our hypothesis and a few previous studies (Pöyhönen et al 2012;Sjögren et al 2020;Thornberg and Jungert 2013), defender self-efficacy was found to be linked to greater reinforcing, even though the link was weak. Thus, low defender self-efficacy does not only inhibit defending and increases the risk that students remain passive as bystanders (e.g., Thornberg and Jungert 2013;Thornberg et al 2017) but also that they laugh and cheer on the bullies.…”
Section: Defender Self-efficacysupporting
confidence: 92%
“…In accordance with our hypothesis and the very few previous studies (Gini 2006;Sjögren et al 2020;Thornberg and Jungert 2013), it was found that moral disengagement was positively associated with reinforcing, suggesting that students with a stronger tendency to morally disengage in bullying situations are more inclined to laugh and cheer on the bullies when witnessing school bullying. In other words, moral disengagement is not only linked to greater bullying perpetration (Gini et al 2014) but also to a bystander behavior that previous studies have shown to be associated with a higher bullying prevalence among classmates (Kärnä et al 2010;Nocentini et al 2013;Salmivalli et al 2011;Thornberg and Wänström 2018).…”
Section: Moral Disengagementsupporting
confidence: 92%
See 2 more Smart Citations
“…Without having a strong belief in one's ability to help victims, intervention would be unlikely. In line with this tenet, previous research has found defender self‐efficacy to be associated with greater defending and less passive bystanding (e.g., Pronk et al, 2013; Sjögren, Thornberg, Wänström, & Gini, 2020; Thornberg et al, 2017).…”
Section: Introductionmentioning
confidence: 56%